Cercopithecid fossils from Kanapoi, West Turkana, Kenya (2007–2015). Issue 140 (March 2020) - Frost, Stephen R.; Ward, Carol V.; Manthi, Fredrick K.; Plavcan, J. Michael
Abstract: Recent fieldwork at Kanapoi has expanded the sample of fossil cercopithecids, facilitating a re-appraisal of their taxonomy. The assemblage now includes at least one species of cercopithecin, two papionins, and two colobines. The guenon Nanopithecus browni is similar in dental size to extant Miopithecus . We tentatively re-affirm the identification of Parapapio cf. ado and confirm the presence of Theropithecus . The colobines include a small form tentatively attributed to Kuseracolobus and a second larger species. The Kanapoi fossils represent the oldest occurrences of guenons in Africa and of the important genus Theropithecus, the most abundant and widespread primate in the Neogene of Africa. In the assemblage, Parapapio cf. ado is the most abundant form, comprising the majority of specimens. All of the other taxa are comparatively rare. Colobines make up a small part of the Kanapoi fossil assemblage compared to most other contemporary sites, including Allia Bay, Kenya, where, like Kanapoi, Australopithecus anamensis has been found. The presence of Theropithecus is consistent with the presence of some relatively open habitat at Kanapoi. While the ecological preferences of the small cercopithecin are unknown, most guenons are associated with relatively wooded habitats, as are most colobines, suggesting the availability of at least some wooded areas.